A Novel α-Galactosidase A Splicing Mutation Predisposes to Fabry Disease - Li, Ping; Zhang, Lijuan; Zhao, Na; Xiong, Qiuhong; Zhou, Yong-An; Wu, Changxin; Xiao, Han (Frontiers in Genetics, 2019)
Fabry disease (FD), a rare X-linked α-galactosidase A (GLA) deficiency, resulting in progressive lysosomal accumulation of globotriaosylceramide (Gb3) in a variety of cell types. Here we report a novel splicing mutation (c.801+1G>A) that results in alternative splicing in GLA of a FD patient with variable phenotypic presentations of renal involvement. Sequencing of the RT-PCR products from the patient’s blood sample reveals a 36-nucleotide (nt) insertion exists at the junction between exons 5 and 6 of the GLA cDNA. Splicing assay indicates that the mutated minigene produces an alternatively spliced transcript which causes a frameshift resulting in an early termination of protein expression. Immunofluorescence shows puncta in cytoplasm for mutated GLA whereas uniform staining small dots evenly distributed inside cytoplasm for wild type GLA in transfected HeLa cells. The increased senescence and decreased GLA enzyme activity suggest that the abnormalities might be due to the altered localization which further might result from the lack of the C-terminal end of GLA. Our study reveals the pathogenesis of splicing mutation c.801+1G>A to FD and provides scientific foundation for accurate diagnosis and precise medical intervention for FD.